A midsummer night's dream : language and writing - White, R.S. (New York : The Arden Shakespeare, 2020)
"This lively and informative guide to Shakespeare's popular comedy equips you with the critical skills to analyse its language, structure and themes and to expand and enrich your own response to the play. A Midsummer Night's Dream is a perfect play for exploring Shakespeare's diverse uses of language to reveal character and themes, from formal iambics and rhyming couplets of courtiers and lovers, and 'warbling' notes' and nursery rhythms of fairies, to stocky prose by the artisan players including Bottom's comic malapropisms. An introduction considers when and how the play was written, and addresses the language with which Shakespeare created A Midsummer Night's Dream, as well as the generic, literary and theatrical conventions at his disposal. It then moves to a detailed examination and analysis of the play, focusing on its literary, technical and historical intricacies; an account of the play's performance history and its critical reception completes the volume. Each chapter offers a 'Writing matters' section, clearly linking the analysis of Shakespeare's language to your own writing strategies in coursework and examinations"--
Keywords: Shakespeare, William, -- 1564-1616. -- Midsummer night's dream -- Criticism and interpretation; Shakespeare plays; Shakespeare studies & criticism